Trajectories of Internalizing Problems in War‐Affected Sierra Leonean Youth: Examining Conflict and Postconflict Factors. Issue 2 (24th September 2012) - Betancourt, Theresa S.; McBain, Ryan; Newnham, Elizabeth A.; Brennan, Robert T.
<x xml:space="preserve">Abstract</x> Three waves of data from a prospective longitudinal study in Sierra Leone were used to examine internalizing trajectories in 529 war‐affected youth (ages 10–17 at baseline; 25% female). Latent class growth analyses identified 4 trajectories: A large majority of youth maintained lower levels of internalizing problems (41.4%) or significantly improved over time (47.6%) despite very limited access to care, but smaller proportions continued to report severe difficulties 6 years postwar (4.5%) or their symptoms worsened (6.4%). Continued internalizing problems were associated with loss of a caregiver, family abuse and neglect, and community stigma. Despite the comparative resilience of most war‐affected youth in the face of extreme adversity, there remains a compelling need for interventions that address family‐ and community‐level stressors.